Multidimensional characteristics of the tumor microenviron-ment and advances in targeted delivery strategies - CHEN, Hongdan; ZHANG, Long; LI, Chong (Zhejiang da xue xue bao. Journal of Zhejiang University. Medical sciences. Yi xue ban, 2025)
The tumor microenvironment (TME) is a critical determinant of tumor initiation, progression, and therapeutic response, and serves as the basis for designing precise delivery strategies. Its marked heterogeneity underscores the need for a more comprehensive understanding of its composition and function. In addition to the extensively studied classical TME, emerging evidence highlights the significant roles of the tumor mechanical microenvironment and the tumor microbial microenvironment in modulating treatment efficacy. These non-classical dimensions not only independently influence tumor behavior but also interact dynamically with classical TME components. Mechanical cues within the TME, including matrix stiffness and solid stress, significantly affect drug distribution and treatment efficacy, suggesting that mechanical remodeling represents a potential strategy to enhance therapeutic outcomes. Concurrently, tumor-associated microbiota and their metabolites participate in immune regulation and metabolic reprogramming, contributing to tumor development and offering novel therapeutic targets. Moreover, recent advances have broadened our understanding on the multilayered regulatory landscape of the TME through the investigation of previously underappreciated factors such as neural regulation, metabolic niche dynamics, spatiotemporal heterogeneity, and epigenetic modulation. This review systematically summarizes the characteristics of these diverse TME dimensions and highlights recent progress in targeted delivery strategies, to facilitate the development of more personalized and effective anticancer therapies.